Mobilization and export of millennial-aged organic carbon by the Yellow River - Xue, Yuejun; Zou, Li; Ge, Tiantian; Wang, Xuchen (Limnology and oceanography, 2017)
A combined carbon isotope (13C and 14C) study was carried out to investigate the sources and fate of organic carbon (OC) transported by the Yellow River and preserved in the sediments of the Bohai and Yellow Seas. In 2015, the Yellow River delivered 3.14 × 1010 g C and 4.12 × 1010 g C of dissolved organic carbon (DOC) and particulate organic carbon (POC) to the Bohai Sea. Carbon isotope signatures revealed that the Yellow River transports millennial-aged DOC and POC during all seasons. The values of δ 13C-DOC ranged from −24.7‰ to −28.8‰ in the river basin, and −21.0‰ to −27.0‰ in the lower reach. The 14C ages of DOC were 415–1690 yr before present (BP) in the river basin, and they were relatively constant seasonally (1320–1690 yr BP) in the lower reach of the river. In comparison, POC δ 13C values in the river were less variable (−22.8‰ to −25.0‰), but much older in both the river basin (4960 ± 1690 yr BP) and in the lower reach (4040 ± 1050 yr BP). Calculations using a dual-isotopic three-end member model revealed that biomass OC derived from C₃ plants was the major source of riverine DOC, contributing 65% ± 8% and 52% ± 2% in the river basin and lower reach seasonally. Pre-aged soil OC and fossil OC from weathering contributed 21–42% and 6–14% of the DOC, respectively. In contrast, pre-aged soil OC and fossil OC contributed 60–70% and 17–27% of POC, and biomass OC contributed a minor fraction (13% ± 7%) of riverine POC. Our results further revealed that aged riverine POC had a major influence on OC preservation in the delta and coastal sediments of the Bohai and Yellow Seas. The age of OC in surface sediments varied widely (1610–8275 yr) due to the influence of Yellow River input. Pre-aged soil OC and fossil OC each contributed 32% ± 8% and 22% ± 14% of OC preserved in the sediments. We estimate that about 0.27 Mt yr−1 and 0.07 Mt yr−1 of pre-aged soil OC and fossil OC accumulate in the surface sediments from POC delivered by the modern Yellow River, and 0.013 Mt yr−1 and 0.002 Mt yr−1 of pre-aged soil OC and fossil OC enters the coastal DOC cycle from riverine DOC. The millennial-aged OC delivered to coastal seas by the Yellow River therefore has profound impacts not only on carbon cycling and the carbon budget in the marginal sea, but also on coastal ecosystems and biogeochemical processes.